Evaluation of Cytotoxic Activity of Combination Honey and Aloe Vera in NIH3T3 Fibroblast Cell Lines and Its Effect on Cell Viability - Januar Rizqi; Tia Amestiasih (Global Health Science Group, 2020)
Alternative treatments can be used singly or in mixture to treat and prevent disease. Honey and Aloe vera are natural ingredients that have anti-microbial, anti-inflammatory, antioxidant properties that are used to treat wounds. Animal studies have shown that giving honey and Aloe vera can speed up wound healing time. This study aims to examine the cytotoxic effect of the combination of honey and Aloe vera on the NIH3T3 cell line and its impact on cell viability. This research is a pure experiment using the post-test only design with control group design. The cytotoxicity test was on NIH3T3 fibroblast cells using the MTT Assay method to determine the inhibitory concentration (IC50) value. Cell viability was calculated using the MTT Assay method. The combination is divided into 5 concentrations, combination 1 (2% honey and 500 μg/mL (0.005%) Aloe vera)), combination 2 (1.5% honey and 250μg/mL (0.0025%) Aloe vera)), combination 3 (1% honey and 125 μg/mL (0.00125%) Aloe vera)), combination 4 (Honey 0.5% and 50μg/mL (0.0005%) Aloe vera)), combination 5 (Honey 0.1 % and 0.5μg/mL (0.00005%) Aloe vera)). The combination of honey and Aloe vera showed inhibition below 13.87% with an IC50 value of 6.58%. Combination honey and Aloe vera on average was able to increase the viability of fibroblast cells above 86.13%. Combination 4 and 5 can increase cell viability 96.50% and 99.80%. The combination of honey and Aloe vera does not cause cytotoxic effects on NIH3T3 fibroblasts cell line and can increase the viability of fibroblasts.